PENINGKATAN KEMAMPUAN BAHASA INGGRIS MAHASISWA SEMESTER II STAIN DATOKARAMA PALU MELALUI PAIR-DICTATION - Sahri Sahri; Nurasia Munir (ISTIQRA, 2014)
This research used a quasi-experimental method. The research data were collected by using two types of instrument, which tests and questionnaires for data English language skills of students and data on student interest in learning. The data obtained through these tests were analyzed using T test and the data were analyzed using student interest statistical description. The results showed that the average value of the final test experimental group better is 81.32 classifications are at a very good compared to the average value of the final test in the control group were 71.18 in either classification. Application of pair-dictation and conventional methods have fundamental differences in learning outcomes. The implementation of pair-dictation can improve student` interest in learning English. Data results showed there are 14 students in student interest at the level of very interested and 5 students at the level of interest, it showed most of the students were excited to learn English through pair-dictation strategy. And to the interest of students, there was a significant relationship between English proficiency and interest of students based on student results positively linked to their interest in the experimental group